Musculoskeletal involvement of COVID-19: review of imaging - Ramani, Santhoshini Leela (Skeletal Radiol, 2021)
The global pandemic of coronavirus disease 2019 (COVID-19) has revealed a surprising number of extra-pulmonary manifestations of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection. While myalgia is a common clinical feature of COVID-19, other musculoskeletal manifestations of COVID-19 were infrequently described early during the pandemic. There have been emerging reports, however, of an array of neuromuscular and rheumatologic complications related to COVID-19 infection and disease course including myositis, neuropathy, arthropathy, and soft tissue abnormalities. Multimodality imaging supports diagnosis and evaluation of musculoskeletal disorders in COVID-19 patients. This article aims to provide a first comprehensive summary of musculoskeletal manifestations of COVID-19 with review of imaging.